Local controllability of complex networks - Chang Luo (Mathematical Modelling and Control, 2021)
The control of complex networks has been studied extensively in the last decade, with different control models been introduced. In this paper, we propose a new network control framework, called local controllability. Local controllability extends the entire network control onto a local scale, and it concerns about the minimum number of inputs required to control a subset of nodes in a directed network. We develop a mathematical formulation for local controllability as an optimization problem and show that it can be solved by a cubic-time algorithm. Moreover, applications to both real networks and model networks are presented and results of these numerical studies are then discussed.